Analysis Of The Factors That Influence The Decision to Use Digital Wallets on Gen Z Muslims in Bone in Terms Of Islamic Economic Perspective - Alda Melanie Putria Dewita Sari Naim; Kamiruddin; Otong Karyono (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of Islamic financial literacy and lifestyle on the decision to use digital wallets in gen Z from an Islamic economic perspective. This study uses a quantitative approach with Partial Least Square (PLS) analysis technique. The results showed that Islamic financial literacy has a positive effect on the decision to use a digital wallet, where understanding Islamic financial principles is the basis for choosing digital financial services. Lifestyle is also proven to influence the decision to use digital wallets, with the values of honesty and simplicity characterizing gen Z Muslims in Bone Regency. Simultaneously, sharia financial literacy and lifestyle have a significant effect on the decision to use digital wallets. This finding indicates that the combination of a good understanding of sharia finance and a lifestyle aligned with Islamic values is an important factor in the adoption of digital financial technology among gen Z Muslims